Novel methods for randomizing - Grant, William (Henry Stewart Talks, 2007)
Obstacles to standard methods of restricted randomization, Biased coin methods, Nash equilibrium, The maximal procedure, Covariate adaptive methods, Response adaptive randomization, Predictability and the potential for selection bias, Efficiency of treatment effect estimators, Patient welfare issues, Optimal randomization
Archived at 2018/05/31